Omnibus Law And Conflicting Norms And Their Relevance To Business Ease In Indonesia (Journal of Private and Commercial Law, 2022)
The problem of overlapping laws and regulations in Indonesia has become a classic unresolved issue. The emergence of the Omnibus Law as a new method of drafting legislation in Indonesia is expected to be able to resolve these problems. However, the Constitutional Court (MK) has decided that the Job Creation Act which has been drafted using the Omnibus Law method is conditionally unconstitutional. This study aims to examine in depth the relevance of the Omnibus Law method to the harmonization of legislation in Indonesia and its relation to the Constitutional Court's decision on conditionally unconstitutional. The research method used in this research is normative juridical using secondary data. Based on the results of the study, it is known that the relevance of the Omnibus Law method to the harmonization of laws and regulations in Indonesia is the Omnibus Law method, which offers regulatory reforms that overlap each other even though Law No. 15 of 2019 has not included this concept but harmonization of laws and regulations needs to be done. to resolve conflicting laws and regulations. This method is expected to be able to solve the problems of effective and efficient laws and regulations. It is also necessary to provide a legal basis regarding the Omnibus Law so that these regulations run well and do not cause problems in law enforcement in Indonesia.